Chemical Castration Sanction Against Crimes Of Sexual Violence In Children Reviewing From Criminal Law Aspects - Ibrahim, Muhammad Mirza (UMPurwokerto Law Review, 2022)
Abstract Chemical castration is an effort to enforce the law against perpetrators of violence against children by injecting anti-testosterone into perpetrators whose purpose is to suppress sexual desire to prevent and provide a deterrent effect to perpetrators of crime so as not to repeat similar crimes in the future. The existence of Government Regulation Number 70 of 2020 reaped various reactions, both pros and cons. This research method is normative juridical by examining secondary data as a primary material to research by searching for regulations, literature, and research journals. Chemical castration sanctions in terms of criminal law aspects include the purpose of punishment based on combined theory and paralysis theory, data on crimes of violence against children, legal protection in the form of restitution and compensation, counseling services, medical services, or assistance to children as victims and criminal responsibility for perpetrators. The obstacle to implementing additional sanctions for chemical castration in terms of the criminal law aspect is the executor or executor of the chemical castration action. The executor of chemical castration, in this case, the Doctor through the Indonesian Medical Association (Ikatan Dokter Indonesia, IDI), rejects the act of chemical castration against the perpetrator for violating the Doctor’s Oath and the Medical Code of Ethics. Keywords: Sexual Violence, Chemical Castration, Executor Abstrak Tindakan kebiri kimia merupakan upaya penegakan hukum terhadap pelaku kejahatan kekerasan seksual pada anak dengan cara menyuntikan anti-testosteron kepada pelaku yang tujuannya adalah untuk menekan nafsu seksual, mencegah dan memberikan efek jera kepada pelaku kejahatan agar tidak mengulangi kejahatan yang serupa di masa yang akan datang. Adanya Peraturan Pemerintah Nomor 70 Tahun 2020 menuai reaksi yang beragam baik pro maupun kontra. Metode Penelitian ini adalah yuridis normatif dengan cara meneliti data sekunder sebagai bahan dasar untuk diteliti dengan cara mengadakan penelusuran terhadap peraturan-peraturan, literatur, dan jurnal penelitian. Sanksi kebiri kimia ditinjau dari aspek hukum pidana meliputi tujuan pemidanaan berdasarkan teori gabungan dan teori pelumpuhan, data kejahatan kekerasan terhadap anak, perlindungan hukum berupa pemberian restitusi dan kompensasi, pelayanan konseling, pelayanan atau bantuan medis terhadap anak sebagai korban dan pertanggungjawaban pidana terhadap pelaku. Kendala pelaksanaan sanksi tambahan kebiri kimia ditinjau dari aspek hukum pidana adalah eksekutor atau pelaksana tindakan kebiri kimia. Eksekutor kebiri kimia dalam hal ini Dokter melalui lembaga Ikatan Dokter Indonesia (IDI) menolak adanya tindakan kebiri kimia terhadap pelaku karena melanggar Sumpah Dokter dan Kode Etik Kedokteran. Kata Kunci : Kekerasan Seksual, Kebiri Kimia, Eksekutor.